2023
DOI: 10.1002/jper.23-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scaling and root planing with and without minocycline HCl microspheres on periodontal pathogens and clinical outcomes: A randomized clinical trial

Abstract: BackgroundThis study tests the effects of scaling and root planing (SRP) versus SRP plus minocycline hydrochloride microspheres (SRP+MM) on 11 periodontal pathogens and clinical outcomes in Stage II‐IV Grade B periodontitis participants.MethodsSeventy participants were randomized to receive SRP (n = 35) or SRP+MM (n = 35). Saliva and clinical outcomes were collected for both groups at baseline before SRP, 1‐month reevaluation, and at 3‐ and 6‐month periodontal recall. MM were delivered to pockets ≥5 mm immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The observation of significant changes in HDAC expression exclusively at the 6-month recall could suggest that HDACs tend to reflect the periodontal tissue changes after a longer period, which correlates with continued periodontal healing observed for 6-9 months following NSPT in advanced disease (Arnett et al, 2023;Badersten et al, 1984). Despite the identification of differential HDAC expression in saliva following periodontal treatment, the exact cell types responsible for these changes could not be determined using this methodology (salivary expression), which warrants further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…The observation of significant changes in HDAC expression exclusively at the 6-month recall could suggest that HDACs tend to reflect the periodontal tissue changes after a longer period, which correlates with continued periodontal healing observed for 6-9 months following NSPT in advanced disease (Arnett et al, 2023;Badersten et al, 1984). Despite the identification of differential HDAC expression in saliva following periodontal treatment, the exact cell types responsible for these changes could not be determined using this methodology (salivary expression), which warrants further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, an emerging strategy that involves the synergistic utilization of scaling and root planning (SRP) with the integration of local drug delivery systems (LDDSs) or sustained-release drug delivery techniques ( 67 ). Notably, research has demonstrated that patients receiving adjunctive treatment of scaling and root planning utilizing minocycline hydrochloride microspheres displayed a notable reduction in both counts of periodontal pathogens and levels of periodontal attachment loss, surpassing the outcomes observed in the control group ( 68 ). Nanocarriers offer advantages in enhancing drug solubility and dissolution rate, improving oral bioavailability, and reducing side effects and dosing frequency ( 69 ), and they may have a potential role in improving cognitive function in AD ( 70 ).…”
Section: The Potential Application Of Oral Microbiota In the Preventi...mentioning
confidence: 99%
“…Minocycline microspheres (MM) are approved by the US Food and Drug Administration as an adjunct to mechanical scaling to reduce the depths of periodontal pockets in patients with periodontitis . In the study by Arnett et al, mechanical scaling and MM treatment reduced the number of periodontal pathogens, improved the clinical outcome of patients with periodontitis, and reduced the depths of periodontal pockets when compared to mechanical scaling alone. The preparation methods for microspheres are complicated; additionally, their physical and chemical properties, such as spheroid formation, encapsulation efficiency, and drug loading, are easily affected by the preparation methods, which can cause a burst release effect and adversely influence the therapeutic effect. …”
Section: Introductionmentioning
confidence: 99%